2015
DOI: 10.1039/c4ob02522a
|View full text |Cite
|
Sign up to set email alerts
|

Bichromophoric dyes for wavelength shifting of dye-protein fluoromodules

Abstract: Dye-protein fluoromodules consist of fluorogenic dyes and single chain antibody fragments that form brightly fluorescent noncovalent complexes. This report describes two new bichromophoric dyes that extend the range of wavelengths of excitation or emission of existing fluoromodules. In one case, a fluorogenic thiazole orange (TO) was attached to an energy acceptor dye, Cy5. Upon binding to a protein that recognizes TO, red emission due to efficient energy transfer from TO to Cy5 replaces the green emission obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…As a result, since the scFv HL1.0.1-TO1 was previously isolated against a monomeric fluorogen, we suggest that only one tandem-half of the molecule may actually form the affinity complex rather than the whole-molecule tandem fluorogen. A similar observation was previously determined when using tandem pairings of fluorogen-fluorophore or fluorogenpolyethylene-biotin molecules (Pham et al, 2015;Szent-Gyorgyi et al, 2010;Vasilev et al, 2016). In these three studies, the fluorogen component shows affinity interaction with the scFv irrespective of its tandem fluorogen pair, where most likely both moieties display independent functional activities.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…As a result, since the scFv HL1.0.1-TO1 was previously isolated against a monomeric fluorogen, we suggest that only one tandem-half of the molecule may actually form the affinity complex rather than the whole-molecule tandem fluorogen. A similar observation was previously determined when using tandem pairings of fluorogen-fluorophore or fluorogenpolyethylene-biotin molecules (Pham et al, 2015;Szent-Gyorgyi et al, 2010;Vasilev et al, 2016). In these three studies, the fluorogen component shows affinity interaction with the scFv irrespective of its tandem fluorogen pair, where most likely both moieties display independent functional activities.…”
Section: Introductionsupporting
confidence: 80%
“…Here, the antibody functions as a protein cage that sterically confines the smallmolecule fluorogen, and, upon light excitation, the fluorogen emits fluorescence due to non-radiative energy decay and energy release. Incidentally, FAP technology also offers a malleable approach for altering fluorescence signals, primarily by modifying the chemical composition of the synthetic fluorogens in order to tune their binding affinities and/or spectra (Pham et al, 2015;Rastede et al, 2015;Saunders et al, 2013Saunders et al, , 2014Szent-Gyorgyi et al, 2010). Furthermore, FAP reporters have demonstrated a rapid advancement as tools for labeling targets at the surface of cells (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fluorogen could be linked to a variety of dye acceptors[36], including pH sensors and far-red energy transfer acceptors, producing multicolor labeling reagents. Grover et al prepared a pH senstitive analog of the TO1 dye, which reported in real-time on changes in GPCR endocytosis and intracellular acidification of the endosomes[37].…”
Section: Introductionmentioning
confidence: 99%
“…Rhodanine, [23][24][25] a ve-membered S,N-heterocycle, can serve as a building block for organic dyes in biomedical elds such as biomolecule uorescent labeling, 11 proteomics, 12 photodynamic therapy, [13][14][15] live cell imaging, [16][17][18][19] antitumor drugs, 20 DNA detection, 8 pH probes, 21 uorescent sensors, 22 etc. Owning to their strong electron-withdrawing properties, rhodanine derivatives have been broadly utilized as acceptors for the design of donor-acceptor (D-A) type photovoltaic materials in organic solar cells (OSCs).…”
mentioning
confidence: 99%